Odpowiedź :
a) -7(x+2) +4=-3x
-7-14+4=-3x
-7x+3x= 14 -4
-4x=10/:-4
x= -10
----
4
x= -2 1
--
2
b)1- 2x +5=4/*3
-----
3
3-2x-5=12
-2x=12+5-3
-2x=14/:-2
x=-7
c)-4(1 x -2)-4=2(-x+2)
--
2
-2x+8-4= -2x+4
-2x+2x=4-8
0= -4
równanie sprzezcne
d) 2x(x-1)=2(x-1)(x+3)
2xkwadrat-2x=2(xkwadrat + 3x -x +3)
2xkwadrat-2x=2xkwadrat+6x-2x+6
2xkwadrat-2xkwadrat-2x-6x+2x=6
-6x=6/:-6
x=-1
e) x - x +1 = 1 (x+6) / *6
--- --- ---
2 3 6
3x-2x+6=x+6
3x-2x-x=6-6
0=0
równanie tożsamościowe
f) x -1 - x+1 = - x/*4
------ ----- ---
4 2 4
x-1-2(x+1)=-x
x-1-2x-2=-x
x-2x+x=2+1
0=3
równanie sprzeczne
zad2
a) x = 5
--- ---
2 6
6x=10/:6
x= 10
--
6
x= 1 2
--
3
b)x = x+1
--- ----
2 4
4x=2(x+1)
4x=2x+2
4x-2x=2
2x=2/:2
x=1
c) 2(x-1) = x+2
------- -----
3 5
5*(x-1) = 3(x+2)
10x -10=3x+6
10x-3x=6+10
7x= 16/:7
x= 2 2
--
7
d) x-1 = x
----- ---
x+3 x+1
x(x+3)=(x-1)(x+1)
xkwadrat +3x= xkwadrat-1
xkwadrat-xkwadrat+3x= -1
3x=-1/:3
x= - 1
---
3
e) 2a+1 = a+3
------- -----
2a a-1
2a(a+3)=(2a+1)(a-1)
2akwadrat +6a=2akwadrat-2a+a-1
2akwadrat+6a-2akwadrat+2a-a=-1
7a=-1/:7
a= - 1
---
7
f) b-2 = b
------ ----
b+1 b-3
(b-2)(b-3)=b(b+1)
b kwadrat -3b-2b+6=b kwadrat+b
b kwadrat -3b -2b -b kwadrat -b= -6
-6b=-6/:-6
b=1
mam nadzieję,że rozczytasz to co napisałam
-7-14+4=-3x
-7x+3x= 14 -4
-4x=10/:-4
x= -10
----
4
x= -2 1
--
2
b)1- 2x +5=4/*3
-----
3
3-2x-5=12
-2x=12+5-3
-2x=14/:-2
x=-7
c)-4(1 x -2)-4=2(-x+2)
--
2
-2x+8-4= -2x+4
-2x+2x=4-8
0= -4
równanie sprzezcne
d) 2x(x-1)=2(x-1)(x+3)
2xkwadrat-2x=2(xkwadrat + 3x -x +3)
2xkwadrat-2x=2xkwadrat+6x-2x+6
2xkwadrat-2xkwadrat-2x-6x+2x=6
-6x=6/:-6
x=-1
e) x - x +1 = 1 (x+6) / *6
--- --- ---
2 3 6
3x-2x+6=x+6
3x-2x-x=6-6
0=0
równanie tożsamościowe
f) x -1 - x+1 = - x/*4
------ ----- ---
4 2 4
x-1-2(x+1)=-x
x-1-2x-2=-x
x-2x+x=2+1
0=3
równanie sprzeczne
zad2
a) x = 5
--- ---
2 6
6x=10/:6
x= 10
--
6
x= 1 2
--
3
b)x = x+1
--- ----
2 4
4x=2(x+1)
4x=2x+2
4x-2x=2
2x=2/:2
x=1
c) 2(x-1) = x+2
------- -----
3 5
5*(x-1) = 3(x+2)
10x -10=3x+6
10x-3x=6+10
7x= 16/:7
x= 2 2
--
7
d) x-1 = x
----- ---
x+3 x+1
x(x+3)=(x-1)(x+1)
xkwadrat +3x= xkwadrat-1
xkwadrat-xkwadrat+3x= -1
3x=-1/:3
x= - 1
---
3
e) 2a+1 = a+3
------- -----
2a a-1
2a(a+3)=(2a+1)(a-1)
2akwadrat +6a=2akwadrat-2a+a-1
2akwadrat+6a-2akwadrat+2a-a=-1
7a=-1/:7
a= - 1
---
7
f) b-2 = b
------ ----
b+1 b-3
(b-2)(b-3)=b(b+1)
b kwadrat -3b-2b+6=b kwadrat+b
b kwadrat -3b -2b -b kwadrat -b= -6
-6b=-6/:-6
b=1
mam nadzieję,że rozczytasz to co napisałam